تداولية الفعل الكلامي في ديوان أطلس المعجزات لصالح خرفي. - شودار, سامية (Revues faculté des lettres et des langues; No 16 (2014): مجلة كلية الآداب واللغات)
يسعى هذا المقال إلى دراسة نظرية تداولية، تندرج ضمن تداولية الدرجة الثالثة؛ وهي نظرية الأفعال الكلامية، وقد تأسست هذه النظرية على يد الفيلسوف الانجليزي "أوستين"، ثم قام بتطويرها تلميذه "سيرل"، الذي اقترح تعديلا لتقسيم "أوستين"، ومن خلالها سنحاول دراسة الخطاب الشعري في "أطلس المعجزات لصالح خرفي"، معتمدين في ذلك تقسيم "سيرل"  للأفعال الكلامية؛ والمتمثل في: التقريريات، والوعديات، والتوجيهيات، والتعبيريات، والإعلانيات.   This article seeks to examine the pragmatics theory, fall within the pragmatics third degree; a verbal acts theory, and this theory was founded  by  the English "Austin" philosopher, and developed by his disciple "Searle", Where he presented the latter amendment to the division of his teacher, and through it we will try to study poetic discoursr in favor of  Atlas el Moajizatte from "saleh kharfi" depending on the division," Searle" acts of words, and of Assertive and Promissivs, and Directives and Expressives and Declarativs.